Physiological data of Pacific oyster Crassostrea (Magallana) gigas after exposure to intermittent hypoxia and the combination with (fluctuating) elevated temperature - Torben Bruhns; Stefan Timm; Nina Feußner; Sonja Engelhaupt; Matthias Labrenz; K Mathias Wegner; Inna M Sokolova (PANGAEA, 2025)
Organisms in intertidal zones experience fluctuations in environmental stressors such as hypoxia and temperature. These stressors and their fluctuations often appear in combination. Combination of stressors can have different effects compared to single stressors. In this study, we investigate the physiological effects of intermittent hypoxia in combination with different temperature regimes on the Pacific Oyster Crassostrea (Magallana) gigas. The oysters were exposed to hypoxic cycles (12h hypoxia by emersion/12h submersion) at normal (15°C), elevated (30°C) or fluctuating (15°C submersion/30°C emersion) temperature for 10 days. After the last submersion phase, the gills and digestive gland were sampled. We measured markers for bioenergetics and redox-balance in the gills and digestive gland using colorimetric methods as well as a set of metabolites (predominantly amino acids, osmolytes, anaerobic end products and energetic metabolites) in the gills using LC-MS/MS. Oysters kept submerged for up to 10 days were used as controls.